Green synthesis of zero valent iron nanoparticles using Verbascum thapsus and its Cr (VI) reduction activity. (February 2021) - Saleh, Mohammed; Isik, Zelal; Aktas, Yusuf; Arslan, Hudaverdi; Yalvac, Mutlu; Dizge, Nadir
Abstract: In this study, a facile eco-friendly in-situ synthesis of zero valent iron nanoparticles (ZVI-NPs) using Verbascum thapsus leaf (VTL) as reducing and stabilizing agent was reported. VTL and VTL covered with (VTL-ZVI-NPs) were characterized. Zeta potential of VTL-ZVI-NPs decreased with the increases in the pH. BET analyses exhibited an increase in the surface area of the VTL after the covered process from 1.2399 (for VTL) to 2.3151 m 2 /g (for VTL-ZVI-NPs). SEM images showed that VTL had a morphology of a rod-like or network-like surface. VTL-ZVI-NPs exhibited excellent catalytic activity during the catalytic reduction of Cr (VI). The reduction of Cr (VI) was completely realized for 25 mg/L. The complete reduction of Cr (VI) occurred at the original pH value (5.2) and a dose of 1 g/L after 30 min. The first-order kinetic model was found to be more suitable for the experimental results. Graphical abstract: Unlabelled Image Highlights: Zerovalent iron nanoparticles (ZVI-NPs) was synthesized by Verbascum thapsus leaf (VTL). ZVI-NPs was grown in-situ onto VTL and used for Cr (VI) reduction. The maximum Cr (VI) reduction was 100% at 25 mg/L Cr (VI) concentration for 30 min. The first-order kinetic model was found to be more suitable for the experimental results.